The effectiveness of seasonal investments in European Share Portfolios - Thomas Heidorn; F. Maier; M. Winker (Frankfurt School of Finance & Management, 2017)
In this paper, calendar seasonality patterns are examined from day-of-the-week effect across weekly patterns, monthly analysis and whole-year seasonal strategies such as Sell in May and Halloween effect. The analysis is done across six indices, DAX, MDAX, SDAX, Eurostoxx 50, Stoxx Europe Mid 200 and Stoxx Europe Small 200. The observation period is from 1990 to 2015. The evidence found in this paper cannot support the Monday effect across all Indices. The Sell in May effect and Halloween effect were found to be existent over the whole observation period and being mostly influenced by the absence of investment in August and September.
Keywords: F33; F37; G11; G13; G18; G20; G24; G28; 330; Seasonality; Day-of-the-Week Effect; Sell in May; Halloween Effect; Monday Effect